Gold catalysis: non-spirocyclic intermediates in the conversion of furanynes by the formal insertion of an alkyne into an aryl-alkyl CC single bond - Hashmi, A. Stephen K.; Häffner, Tobias; Yang, Weibo; Schultes, Lara; Rominger, Frank (Chemistry - a European journal, 2012)
It takes al-kynes: The formation of furyl-substituted heterocycles from furanynes with donor groups on the furan-alkyne tether and mechanistic control experiments indicate the involvement of open-chained carbenium ions in the overall insertion of an alkyne into a CC bond, rather than the usual spirocyclic intermediates (see scheme).
Gesehen am 06.09.2018